1987
DOI: 10.1001/archderm.1987.01660350091020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anthralin in the Treatment of Alopecia Areata

Abstract: Anthralin cream 0.5% to 1.0% was used to treat 68 patients with severe alopecia areata. Therapy was relatively well tolerated, although all patients experienced pruritus and local erythema and scaling. Cosmetic response was seen in 17 (25%) of the patients, and was maintained during therapy in 12 (71%) of the 17 cosmetic responders. For the patients treated with 0.5% anthralin, the mean time to response (44 of 66 patients) was 11 weeks; the mean time to cosmetic response (13 of 66 patients) was 23 weeks. Durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…For maximum response, overnight application of 0.5% to 1% ointment is recommended. In other studies, anthralin 0.5% to 1% ointment was used and the rate of cosmetically acceptable hair regrowth ranged from 25% to 75% . Anthralin has not been evaluated specifically in children, and the dose used seems to affect its efficacy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…For maximum response, overnight application of 0.5% to 1% ointment is recommended. In other studies, anthralin 0.5% to 1% ointment was used and the rate of cosmetically acceptable hair regrowth ranged from 25% to 75% . Anthralin has not been evaluated specifically in children, and the dose used seems to affect its efficacy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] For example, the term ''cosmetically acceptable'' has been a commonly utilized term that unduly weighs improvement in the top relative to the sides of the scalp since growth here can camouflage remaining hair loss on the sides of the scalp. [7][8][9][10][11][12][13][14] These guidelines serve to offer several different means of assessing hair loss and growth in alopecia areata: not all are meant to be used in any individual trial. Recognizing that there are two main changes in the hair that occur in alopecia areata ie a decrease in the extent of scalp hair coverage and a decrease in terminal hair density in remaining areas of hair growth, both these characteristics of the hair loss should be part of any primary endpoint for alopecia areata.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators reported a regrowth rate of 50%; cosmetic response, however, was observed in only 25% of the patients. 13 The activity of anthralin was found to be similar to that of azelaic acid, 14 but lower than topical corticosteroids. 15,16 Combination therapy with anthralin and 5% minoxidil shows a synergistic effect in treatment-resistant AA.…”
mentioning
confidence: 92%